Electron emission prom the cathode during the initial phase of a nanosecond vacuum discharge; Russian Physics Journal; Vol. 12, № 5 - Mesyats G. A. Gennady Andreyevich; Bazhenov G. P.; Bugaev S. P.; Proskurovskii D. I.; Rotshtein V. P.; Yurike Ya. Ya. (1969, 1969)
В фонде НТБ ТПУ отсутствует